2008
DOI: 10.3111/13696990802113196
|View full text |Cite
|
Sign up to set email alerts
|

How complicated skin and soft tissue infections are treated in Italy: economic evaluation of inpatient intravenous antibiotic treatment in seven hospitals

Abstract: Efforts should be made to minimise the risk of selecting wrong antibiotics and to identify the quickest antibiotic in eradicating the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Interestingly, the rate of inappropriate initial antibiotic therapy dropped from 43% in 2004 to 3% in 2008 in patients with MRSA cSSTI who presented to emergency departments in a multicenter study; overall rates for patients with cSSTI due to any pathogen were not reported (24). Another difference is that only 16% of patients were hospitalized in that study (24), whereas all were hospitalized in our study and the other studies (6,25,29). In our study, the following factors were predictive of inappropriate initial antibiotic therapy: admission without presentation to the emergency room and cSSTI caused by difficult-to-treat pathogens (i.e., MRSA, both Gram-positive and Gram-negative pathogens, or pathogens other than S. aureus or streptococci).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, the rate of inappropriate initial antibiotic therapy dropped from 43% in 2004 to 3% in 2008 in patients with MRSA cSSTI who presented to emergency departments in a multicenter study; overall rates for patients with cSSTI due to any pathogen were not reported (24). Another difference is that only 16% of patients were hospitalized in that study (24), whereas all were hospitalized in our study and the other studies (6,25,29). In our study, the following factors were predictive of inappropriate initial antibiotic therapy: admission without presentation to the emergency room and cSSTI caused by difficult-to-treat pathogens (i.e., MRSA, both Gram-positive and Gram-negative pathogens, or pathogens other than S. aureus or streptococci).…”
Section: Discussioncontrasting
confidence: 51%
“…These rates are slightly lower than the 22%- to-23% range in other analyses of patients hospitalized with cSSTI, including two retrospective cohort studies (6, 29) and a microcosting study (25). Interestingly, the rate of inappropriate initial antibiotic therapy dropped from 43% in 2004 to 3% in 2008 in patients with MRSA cSSTI who presented to emergency departments in a multicenter study; overall rates for patients with cSSTI due to any pathogen were not reported (24).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In a smaller retrospective study, the authors demonstrated a greater likelihood of hospital readmission or death within 30 days in the subset of cSSTI patients with decubitus ulcers who received inappropriate initial antibiotic therapy (adjusted OR 11.76; 95% CI 1.30–111.11; p 0.03) . Furthermore, inadequate initial antibiotic therapy can increase length of hospital stay and costs . In a retrospective Italian study, failure of initial treatment in cSSTIs was estimated to cost €7835 versus €4989 when the initial antibiotic led to clinical success without the need for further IV treatment .…”
Section: Importance Of Appropriate Initial Antibiotic Therapymentioning
confidence: 98%
“… isolated S. aureus from the majority (71.1%) of infections, followed by β ‐haemolytic streptococci (10.5%) and enterococci (9.3%) . Data from an Italian study identified the Enterobacteriaceae Proteus mirabilis in 1% of cSSTIs in a population of hospitalized patients . Although less frequent, other non‐bacterial microbes can lead to cSSTIs, particularly in travellers, and, in certain circumstances, it is important to consider fungal causes, such as invasive aspergillosis, mucormycosis and other mycoses in immunocompromised patients .…”
Section: Mrsa: An Important Pathogen In Europementioning
confidence: 99%